Drawing degree zero the line from minimal to conceptual art - Lovatt, Anna ca. 20. Jh (The Pennsylvania State University Press, 2019)
"Examines the centrality of drawing to the art of the late 1960s and early 1970s. Focuses on the work of Mel Bochner, Rosemarie Castoro, Sol LeWitt, Dorothea Rockburne, and Richard Tuttle"--Provided by publisher
Keywords: Tuttle, Richard -- 1941-; Bochner, Mel -- 1940-2025; Castoro, Rosemarie -- 1939-2015; LeWitt, Sol -- 1928-2007; Rockburne, Dorothea -- 1934-; Geschichte 1965-1975; Concept-art; Ästhetik; Zeichnung; Minimal Art; USA; Drawing, American / 20th century; Drawing, American; 1900-1999